Socio-Legal Analysis of Early Marriage Phenomenon during the COVID-19 Pandemic in Jombang Regency - Agustiawan, M. Hendri; Mutahhirah, Nazhifatum (Asketik: Jurnal Agama dan Perubahan Sosial, 2023)
The enactment of Law Number 16 of 2019 Concerning Marriage is the government’s efforts to reduce early marriage, but has not achieved the optimal effect. The number of early marriages is increasing, especially during the Covid-19 pandemic. This paper aims to analyze the factors behind the Increasing Phenomenon of Early Marriage in Jombang Regency During The Covid 19 Pandemic and to explain the Consideration of Jombang Religious Court Judge's Decision regarding the Application for Marriage Dispension. This study was conducted empirically using a sociolegal approach, in which social action theory is an analytical tool. The results of this study indicate that the sharp increase in the rate of early marriage in the Jombang regency during the pandemic period is a complex issue involving many factors, including social problems, misuse of technology, the influence of social media, culture, and religion, as well as the lack of parental supervision. The judge's consideration regarding the application for marriage dispensation is to decide whether to grant the petition based on the impact of the gains that can be achieved and the harms that can be avoided.